Modelling Indian wheat and rice sector policies - Marta Kozicka; Matthias Kalkuhl; Shweta Saini; Jan Brockhaus (University of Bonn, Center for Development Research (ZEF), 2015)
This paper serves to disentangle the complex system of Indian food policies related to wheat and rice procurement, storage, distribution and trade. Using nationally aggregated time series data, these policies are econometrically analysed. Based on the estimation results, their market implications are assessed. Eventually, different scenarios, including the implementation of the National Food Security Act, are simulated with respect to fiscal costs and public stocks.
Keywords: Q02; Q18; Q13; I38; H42; O13; 330; India; stocks; fiscal costs; food grain policies; NFSA; wheat; rice